Biological maturation and match running performance: A national football (soccer) federation perspective. Issue 10 (October 2019) - Lovell, Ric; Fransen, Job; Ryan, Rhearne; Massard, Tim; Cross, Rebecca; Eggers, Tahleya; Duffield, Rob
Abstract: Objectives: To examine the influence of maturation and its interaction with playing position upon physical match performances in U15 footballers from a national federation. Design: Observational study. Methods: 278 male outfield players competing in a national tournament were assessed for somatic maturity and match physical performances according to playing position. Stature, sitting height, and body mass were measured and entered into an algorithm to estimate the age at peak height velocity (APHV). Players match movements were recorded by Global Positioning System devices (10 Hz), to determine peak speed, and total- (TD), low-speed running (LSR; ≤13.0 km h −1 ), high-speed running (HSR; 13.1–16.0 km h −1 ), very high-speed running (VHSR; 16.1–20.0 km h −1 ) and sprint distances (SPR; >20.0 km h −1 ) expressed relative to match exposure (m min −1 ). Results: Linear-mixed models using log transformed response variables revealed a significant contribution of estimated APHV upon TD (1.01; 95% CI: 0.99–1.02 m·min −1 ; p < 0.001), HSR (1.05; 95% CI: 0.98–1.13 m min −1 ; p < 0.001) and VHSR (1.07; 95% CI: 1.00–1.14 m min −1 ; p = 0.047). An increase by one year in APHV was associated with an increase of 0.6, 5.4 and 6.9% in TD, HSR and VHSR respectively. No effects of APHV were observed for LSR, SPR, and peak speed. Further, no APHV effects were observed relative to players' field position. Conclusions: Later maturing players covered substantially more higher-intensity (HSR and VHSR) running in matches, irrespective of playing position. The greater match intensity of later maturing players may inform talent identification and athletic development processes within a national federation.